DIGITAL ANALYSIS OF TOOTH SIZES AMONG INDIVIDUALS WITH DIFFERENT MALOCCLUSIONS: A STUDY USING THREE-DIMENSIONAL DIGITAL DENTAL MODELS - Batista Pérez, Adriana; Torres León, Domenica Estefania; Mendez Guevara, Christian David; Moreno Orellana, Nube Fernanda; Bravo Calderon, Manuel Estuardo (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2024)
The objective of the study was to examine the sizes of teeth, in digital models of patients with different malocclusions, with the help of three-dimensional measurement software. 68 digital models of 34 patients aged between 21 and 29 years were analyzed. A review was carried out to determine the participants according to Angle's classification, leaving 24 patients in the class I group and 10 patients in the class II group. Then, the patients' plaster models were scanned, using the Dentsply Sirona Cerec Omnicam Software 5.2 digital scanner, thus obtaining their digital format. NemoStudio-2022 software was then used to perform tooth size measurements. After analysis of the measurements, it was observed that the anterior and general mesiodistal sizes were not statistically related to the different malocclusions. There was also no difference between the groups in terms of values of the previous proportion, nor when evaluating the values of the general proportion between the groups. Finally, no malocclusion group had a significant relationship with the alteration of anterior or general mesiodistal size. The difference in mesiodistal tooth size of the antero-upper and antero-inferior teeth does not contribute to the appearance of Angle Class I, Class II and Class III malocclusions since there were no statistically significant relationships in this regard.